Automated web pages classification with independent component analysis - Sam, Lee Zhi; Maarof, Mohd. Aizaini; Selamat, Ali (2006)
Automated web pages classification becomes an essential tool to reduce the manpower and time consuming for manually categorize web pages. In this paper, we propose a new method of web page classification which uses the output vector of Independent Component Analysis (ICA) and Class Profile Based Feature (CPBF) as input for ANN to do classification.